Técnicas genéticas en la solución de un problema minero - Belette-Fuentes, Orlando; Zamora-Matamoros, Rafael; Caballero-Echevarría, Daimel (DYNA, 2017)
A mathematical model’s system for optimizing the efficiency for sampling exploration and exploitation networks in lateritic nickel and cobalt deposits, located in the north-eastern province of Holguin, was developed in the “Centro de Investigaciones del Níquel”. This system includes a new reservoir model based on multivariate substantial classification using the Markov model for discrete stochastic processes. As a result of the application of these models a linear optimization problem was obtained comprising an objective function, several constraints as inequalities and an additional restriction in the form of equality linked to the number of wells to be selected. The generated problem has polynomial computational complexity and because no accurate methods exist to solve it, an automated tool that brings up feasible solutions was developed based on genetic algorithms.